The emperor's code - Korman, Gordon (39 clues, 2010)
As the race to find the 39 Clues builds to its explosive finish, Amy and Dan must explore an ancient culture and steal a clue guarded by thousands of the world's best-trained soldiers. It's the most dangerous search yet ... and it may mean the end for Amy and Dan.